2007
DOI: 10.2166/nh.2007.024
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation in distributed hydrological modelling: comparison of global and local optimisation techniques

Abstract: Much research has been spent in the last three decades in developing more effective and efficient automatic calibration procedures and in demonstrating their applicability to hydrological problems. Several problems have emerged when applying these procedures to calibration of conceptual rainfall -runoff and groundwater (GW) models, such as computational time, large number of calibration parameters, parameter identifiability, model response surface complexity, handling of multiple objectives and parameter equif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…They generally follow populationbased search strategy. Therefore, they start searching by generating an initial population rather than a single solution as in the case of local optimization [10].…”
Section: Chapter 2 2 Global Optimization Techniques: Genetic Algorithmentioning
confidence: 99%
“…They generally follow populationbased search strategy. Therefore, they start searching by generating an initial population rather than a single solution as in the case of local optimization [10].…”
Section: Chapter 2 2 Global Optimization Techniques: Genetic Algorithmentioning
confidence: 99%
“…Global calibration techniques, such as the Shuffled Complex Evolution (SCE) algorithm by Duan et al (1992), have been successfully applied in some calibration studies of distributed models (Madsen, 2003;Mertens et al, 2004;Blasone et al, 2007a). To reach convergence, global methodologies require a larger number of model runs than local gradient-based techniques, which have also been employed in conjunction with this type of models (Sonnenborg et al, 2003;Blasone et al, 2007a). On the other hand, it has been demonstrated that local procedures have a high probability of converging to suboptimal solutions when they are applied to integrated, distributed models (Blasone et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…To reach convergence, global methodologies require a larger number of model runs than local gradient-based techniques, which have also been employed in conjunction with this type of models (Sonnenborg et al, 2003;Blasone et al, 2007a). On the other hand, it has been demonstrated that local procedures have a high probability of converging to suboptimal solutions when they are applied to integrated, distributed models (Blasone et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Historically and under consideration of the available computational power, model calibration was manually performed by adjusting model parameters with a more or less trial and error process. This approach has been widely used for several complex regional models, e.g., [11][12][13]. However, manual calibration is time-consuming, tedious and very subjective in nature [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, manual calibration is time-consuming, tedious and very subjective in nature [14]. The accuracy of results from this approach requires good experience of the modeller and thorough understanding of the system and is also characterized by the strategies employed to adjust the model parameters [13]. In recent times, manual calibration has been partly substituted by automated approaches, which are also recognized as nonlinear parameter estimation techniques [15].…”
Section: Introductionmentioning
confidence: 99%